Investigação dos imunomoduladores produzidos por astrócitos derivados de células-tronco de pluripotência induzida (hIPSCs) de pacientes com esquizofrenia - Pablo Leal Cardozo (2018)
Schizophrenia is a psychiatric disorder, caused by a conjunction of genetic, environmental and developmental factors. Individuals bearing this disease exhibit cognitive deficits, positive (psychosis, hallucinations and delusions) and negative symptoms (depression, disordered thoughts and speech and loss of social drive), as well as reduced gray matter volume. Microanatomical analyses suggest that this gray matter reduction is due to diminished dendritic spine density. This decrease in spine density observed in schizophrenic patients likely happens because of exaggerated synaptic elimination, a process that normally occurs during adolescence and early adulthood. Recently, it has been shown that immune molecules, such as components of the classical complement cascade and CX3CL1/CX3CR1 pathway, play a direct role in this process, triggering the phagocytosis of immature synapses by microglia. Moreover, it has been demonstrated that astrocytes secrete cytokines capable of modulating the complement cascade and promoting synaptic pruning. Taking into account that pre-natal infection acts as a risk factor for schizophrenia, this work aimed at analyzing cytokines and CX3CL1 production employing induced pluripotent stem cells (hIPSCs)-derived astrocytes from schizophrenic individuals after stimulation with TNF-α. The results demonstrate that TNF-α and IL-1β transcripts production kinetics are altered in schizophrenic-derived (SCZ) astrocytes relative to healthy control-derived (HC) astrocytes. Also, SCZ astrocytes produce increased basal levels of TGF-β3 and delayed CX3CL1 transcription kinetics relative to those of HC. Finally, non-secreted CX3CL1 levels seems to be increased in SCZ astrocytes, suggesting problems in the release of the soluble form. Even though these results should be regarded as preliminary due to the limited sample size, they clearly indicate that SCZ astrocytes produce immunomodulators in a distinct manner compared to HC astrocytes.